Income Tax and VAT Review as Evaluation of Tax Obligations - I Kadek Yoga Sanjaya; I N Darmayasa; I N Mandia (Jurusan Akuntansi Politeknik Negeri Bali, 2020)
This research aims to provide a further understanding on the matter of (1) the condition of tax compliance of income tax and VAT on foreign services, (2) contingent liabilities arising after a review of tax obligations. The data used in this research are primary data such as interviews about the general description of the company and tax obligations, while secondary data in the form of general ledgers, commercial financial reports, reported tax return and other tax supporting documents. The method used for this research is qualitative method as a case study. The tax review performed is a review of the income tax article 21, income tax article 23, income tax article 4 paragraph 2, income tax article 26, corporate income tax and VAT on foreign services. The conclusion of this research are (1) the condition of tax compliance on PT BCL was still classified as under comply both in accordance with national and international assessment standards; (2) contingent liabilities arise marked by a discrepancy between the value of the reported tax object and the value of the tax object based on the review until the delay in payment and reporting tax obligations.